2011
DOI: 10.1186/1742-4755-8-35
|View full text |Cite
|
Sign up to set email alerts
|

Mother-to-child transmission of human immunodeficiency virus in aten years period

Abstract: Objectivesto evaluate mother-to-child transmission (MTCT) rates and related factors in HIV-infected pregnant women from a tertiary hospital between 2000 and 2009.Subjects and methodcohort of 452 HIV-infected pregnant women and their newborns. Data was collected from recorded files and undiagnosed children were enrolled for investigation. Statistical analysis: qui-square test, Fisher exact test, Student t test, Mann-Whitney test, ANOVA, risk ratio and confidence intervals.ResultsMTCT occurred in 3.74%. The stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
13
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 38 publications
5
13
0
1
Order By: Relevance
“…A low CD4 count is an indicator of high viral load. Although, maternal HIV viral load and CD4 counts were not systematically recorded in this study, other studies [19,20] had reported similar findings, indicating mothers with CD4 count less than 200 cells/µl and high viral load (an indication of late AIDS stage) were three to five times more likely to transmit HIV to their exposed infants [9,19,21].…”
Section: Discussionsupporting
confidence: 58%
“…A low CD4 count is an indicator of high viral load. Although, maternal HIV viral load and CD4 counts were not systematically recorded in this study, other studies [19,20] had reported similar findings, indicating mothers with CD4 count less than 200 cells/µl and high viral load (an indication of late AIDS stage) were three to five times more likely to transmit HIV to their exposed infants [9,19,21].…”
Section: Discussionsupporting
confidence: 58%
“…The decline in mortality due to AIDS in Brazil since the 2000s [3], with increasing survival among HIV-infected individuals [46,47], is one possible explanation. The high proportion of pregnant women with diagnoses of HIV infection prior to the current pregnancy, which has been reported in several national studies [11,13,14,18,19], suggests that women who have been infected for longer periods are becoming pregnant, which may also explain the increase in prevalence with age.…”
Section: Discussionmentioning
confidence: 99%
“…The estimated vertical transmission rate was 6.8% in 2004, with a range from 13.4% in the North region to 4.3% in the Midwest region [10]. Local studies conducted in the Southeast region [11-14] have reported vertical transmission rates closer to 3%, while rates of less than or equal to 2% have been found in the Midwest and South regions [15-17]. In contrast, in the North and Northeast regions and in the state of São Paulo, local studies have found vertical transmission rates of 9.9% [18], 9.2% [19] and 6.0% [20], respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Risk factors for HIV infection in the general population of Brazil have been evaluated in several studies . Sexual transmission is the cause of the majority of HIV/AIDS cases in Brazil, with almost half of infections attributable to unprotected sex among men who have sex with other men (MSM).…”
Section: Introductionmentioning
confidence: 99%